2000
DOI: 10.1016/s0002-9440(10)64747-5
|View full text |Cite
|
Sign up to set email alerts
|

APC Mutations in Sporadic Medulloblastomas

Abstract: The cerebellar medulloblastoma (WHO Grade IV) is a highly malignant, invasive embryonal tumor with preferential manifestation in children. Several molecular alterations appear to be involved, including isochromosome 17q and the p53, PTCH, and ␤-catenin gene mutations. In this study, 46 sporadic medulloblastomas were screened for the presence of mutations in genes of the Wnt signaling pathway (APC and ␤-catenin). Single-strand conformational polymorphism (SSCP) analysis followed by direct DNA sequencing reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
145
0
4

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 243 publications
(152 citation statements)
references
References 30 publications
3
145
0
4
Order By: Relevance
“…Although beta-catenin is frequently mutated in medulloblastoma and was recently proposed a prognostic factor for medulloblastoma (4), our medulloblastoma sample did not demonstrate mutations of beta-catenin, but showed allelic imbalance at both APC's exons. This finding is not unusual since many investigations (11,13,28) collectively demonstrated that approximately 15% of medulloblastomas harbor mutations in APC, betacatenin or Axin. These mutations are mutually exclusive which is supported with our result.…”
Section: Resultsmentioning
confidence: 59%
“…Although beta-catenin is frequently mutated in medulloblastoma and was recently proposed a prognostic factor for medulloblastoma (4), our medulloblastoma sample did not demonstrate mutations of beta-catenin, but showed allelic imbalance at both APC's exons. This finding is not unusual since many investigations (11,13,28) collectively demonstrated that approximately 15% of medulloblastomas harbor mutations in APC, betacatenin or Axin. These mutations are mutually exclusive which is supported with our result.…”
Section: Resultsmentioning
confidence: 59%
“…Another report failed to reveal any somatic mutations in 49 MBs regardless of whether or not MB was associated with Turcot syndrome (Mori et al, 1994). Two groups have found missense mutations of APC in the 4/143 tumors analysed, but there was no loss of the wild-type allele (Huang et al, 2000;Koch et al, 2001). One of the germline mutations found was the E1317Q 'subpolymorphic' variant that has been described in association with a predisposition to colorectal tumors as it was found in 4/164 patients with multiple colorectal tumors but not in 160 control alleles (Frayling et al, 1998).…”
Section: Introductionmentioning
confidence: 98%
“…In these tumors, b-catenin is postulated to act as an oncogene. MBs have also been shown to harbor these types of missense mutations in bcatenin (Zurawel et al, 1998;Eberhart et al, 2000;Huang et al, 2000). Both active WNT signaling and activating mutations of b-catenin can result in the accumulation of nuclear b-catenin.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] Several studies have also shown that b-catenin can be oncogenically activated by direct genetic mutation of the phosphorylation sites in exon 3, by the inactivation of GSK-3b, Axin and APC or by the activation of Wnt signaling pathways. [15][16][17] Recently, Wnt family members have been demonstrated to contribute to lymphopoiesis at early stages of both B-and T-cell development. In fact, Wnt signaling through b-catenin has a positive role in the control of T-cell development, such that an absence or reduction in the Wnt signal leads to a reduction in cell proliferation rate and differentiation to the CD4 þ CD8 þ double-positive stage, whereas increased Wnt signaling through stabilization of b-catenin enables differentiation of thymocytes in the absence of a pre-TCR signal.…”
mentioning
confidence: 99%